Hasil tajam pengelihatan pasca operasi katarak senilis di RSUP Sanglah Denpasar periode Oktober 2016 - Juni 2017 - Anak Agung Gde Arisena Asmara; Putu Budhiastra; Ni Ketut Niti Susila (Intisari Sains Medis, 2019)
Introduction: Cataract is a type of eye disease that occurs in the lens of the eye. Cataract occurs not only due to the age factor, but also can occur in children born with these conditions or congenital factors. This study aimed to find out visual acuity outcome after senile cataract surgery at RSUP Sanglah Denpasar on October 2016 - June 2017 period.Method: The type of this research was descriptive cross-sectional conducted at RSUP of Sanglah Denpasar using the medical records of the period of October 2016 - June 2017. The sampling technique used the total sampling, with the number of samples of 32 subjects. The result of this research was processed by using a computer software.Result: The postoperative patients with poor outcome tended to be experienced by the senile cataract of mature group compared to the immature that was around 9.1%, borderline outcome tended to be experienced by group with immature senile cataract of 23.8% while the dominant senile cataract outcome was 81.8%. Patients undergoing SICS procedures tended to have a poor outcome compared to those undergoing a phacoemulsification procedure of 16.7%. Borderline outcome tended to the group undergoing phacoemulsification procedures, and 83.3% of the good outcome tended to be experienced by the group undergoing SICS procedures.Conclusion: This research concludes that good outcome come from cataract senile mature group (81.8%) and the group that doing SICS procedure (83.3%)